Learn, Experience, Reflect Framework for Training Design. (September 2022) - Militello, Laura; Sushereba, Christen; Fernandez, Rosemarie; Wolf, Steve; Winner, Jennifer
The Learn, Experience, Reflect framework for training design provides a structure for communication and collaboration among researchers, trainers, training designers, and technology developers. The framework was articulated in the context of efforts to develop effective recognition skills training for combat medics using augmented reality technology. The Learn component presents didactic information to extend and refine learners' existing mental models. The Experience component leverages augmented reality to provide opportunities to practice applying learned concepts in context. The Reflect component is designed to help learners reflect on their own knowledge to highlight and address knowledge gaps.